Work-Life Balance Among Women Anganwadi Workers in Bengaluru - Sudhindra, Sarayu; Vasanth Kumar, G.; Valarmathi, B. (Prabandhan: Indian Journal of Management, 2020)
Over the past few years, work–life balance has evolved into a matter of significant concern. Both men and women strive to achieve a steady professional and personal life. In reality, women are more prone to experiencing such challenges. The paper attempted to understand work-life balance among Anganwadi workers (women-dominant centres). The research focused on the impact of job satisfaction, work overburden, workplace support, family support, and dependent care on the work-life balance of Anganwadi workers. For the purpose of the study, a structured questionnaire was administered to 467 participants. Statistical technique used for the study was regression model. The results indicated that workplace support and family support had a positive impact on the work–life balance among Anganwadi workers. The findings also suggested that work overburden and dependent care had a negative impact on work-life balance. The results also contradicted the hypotheses by portraying that job satisfaction was not a significant factor that impacted the work-life balance among Anganwadi workers. However, many other variables such as emotional intelligence, job autonomy, turnover intention, absenteeism, and work engagement - that could potentially impact work-life balance - were not taken into consideration.